Recent Development and Advancement in Quantum Dots in Pharmaceutical and Biomedical Fields for the Delivery of Drugs - Singh, Pranjal K.; Singh, Smita; Sachan, Kapil; Verma, Vikrant; Garg, Sakshi (Current Nanoscience, 2024)
Nanoscale semiconductors known as quantum dots (QDs) are essential for drug testing because they bridge the gap between nanotechnology and the testing of drugs. QDs are a valuable tool in theranostics and treatment because of their unique physicochemical features. Due to their photoluminescence and electronic properties, including broad and continuous absorption spectra, narrow emission spectra from visible to near-infrared wavelengths, and long-lasting and high brightness, they are suitable probe materials for use in (bio)sensing (immunological) platforms. Several studies use QDs due to their optical, magnetic, electrical, photochemical, and biological features that allow them to be employed in various scientific domains. When utilized in drug delivery systems, fluorescent markers, such as QDs, can track the metabolism of drugs in the human body. Many medicinal applications, such as disease diagnosis and medication research, can benefit from these fluorescent tests. In this review article, the application of QD in drug delivery and immunoassay sensing has been described in detail.
Keywords: imaging